2019
DOI: 10.1016/j.tws.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Design of prestressed cold-formed steel beams

Abstract: Structural design rules for prestressed cold-formed steel beams, considering both the prestressing and imposed vertical loading stages, are presented herein. In the proposed approach, the cold-formed steel member is designed as a beam-column using linear interaction equations in conjunction with the Direct Strength Method (DSM), while the prestressed cable is designed by ensuring that its tensile capacity is not violated during the two loading stages. In the present paper, the design approach and the failure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The design equations have been reported by Hadjipantelis et al 51 ; in the same study, the reliability and practical implementation of the design recommendations are also demonstrated. In summary, the cold-formed steel beam is designed as a beam-column member using linear interaction equations, which account for the combination of compressive and bending actions, in conjunction with the Direct Strength Method 52,53 , which is used to predict the capacity of the steel member under pure axial compression, negative bending and positive bending.…”
Section: Prestressed Beamssupporting
confidence: 64%
See 2 more Smart Citations
“…The design equations have been reported by Hadjipantelis et al 51 ; in the same study, the reliability and practical implementation of the design recommendations are also demonstrated. In summary, the cold-formed steel beam is designed as a beam-column member using linear interaction equations, which account for the combination of compressive and bending actions, in conjunction with the Direct Strength Method 52,53 , which is used to predict the capacity of the steel member under pure axial compression, negative bending and positive bending.…”
Section: Prestressed Beamssupporting
confidence: 64%
“…Overall, Hadjipantelis et al 50 reported ultimate moment capacity enhancements of up to 40% and decreases in the overall downwards deflections approaching 60%. Prestressed cold-formed steel beams can be designed by adapting existing design methods, as established by Hadjipantelis et al 51 In the proposed design method, the load-carrying capacities of both the steel beam and the cable need to be checked at each of the two loading stages independently. In Stage 1, the beam is subjected to combined axial compression and negative (hogging) bending, both actions due to the prestressing, while in Stage 2 it is subjected to combined axial compression and positive (sagging) bending, due to the prestressing and gravity loading.…”
Section: Prestressed Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the control of raw material quality in this small-medium enterprise is still low, that the use of raw materials is still below the smallest standardized thickness, as a result, the resulting profile is relatively less rigid and below the predetermined standard. The improved rigidity of the lightweight steel profile can be done by modifying web forms and addition folds at the end of lips flanges [8][9][10][11][12][13][14][15][16]. The strength of a structure is determined by the stiffness and flexibility of the beams.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of prestressing steel structures was first investigated by Magnel [3], who suggested that considerable material and therefore cost savings can be achieved from the utilization of prestressed high-strength steel cables in conjunction with structural mild steel members. Subsequent research has focused on prestressed hot-rolled [4,5,6,7] and cold-formed [8,9,10] steel beams, stayed columns [11,12,13,14,15], trusses [16,17,18,19] and stressed-arch frames [20,21].…”
Section: Introductionmentioning
confidence: 99%